2017
DOI: 10.22146/agritech.16767
|View full text |Cite
|
Sign up to set email alerts
|

Efek Hipoglikemik Kecambah Beras Merah pada Tikus yang Diinduksi STZ-NA dengan Parameter Kadar Insulin, Indeks HOMA-IR dan HOMA β (Hypoglycemic Effect of Red Rice Germ on Insulin Levels, HOMA-IR, and HOMA β Index of STZ-NA Induced Rats)

Abstract: ABSTRAKProses perkecambahan biji-bijian seperti beras dapat meningkatkan beberapa nilai gizi seperti asam amino dan serat pangan. Beras merah dan kecambahnya diyakini mampu menurunkan glukosa darah pada penderita diabetes melitus (DM). Tujuan penelitian ini adalah mengevaluasi efek hipoglikemik kecambah beras merah pada tikus diabetes yang diinduksi STZ-NA terhadap kadar glukosa darah, insulin, serta indeks HOMA-IR dan HOMA β. Penelitian ini bersifat eksperimental in vivo pada hewan coba tikus Wistar jantan us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
3
1
0
2
Order By: Relevance
“…This is related to disturbances in cells that reduce insulin synthesis and secretion due to STZ-NA induction in this study was evidenced by the P1 group that was induced by STZ-NA and fed standard feed without any intervention having decreased insulin levels. This statement is in line with previous studies that proved insulin levels in the DM rat group after STZ-NA induced decreased compared to the group without induction (Nurhidajah & Nurrahman, 2017).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is related to disturbances in cells that reduce insulin synthesis and secretion due to STZ-NA induction in this study was evidenced by the P1 group that was induced by STZ-NA and fed standard feed without any intervention having decreased insulin levels. This statement is in line with previous studies that proved insulin levels in the DM rat group after STZ-NA induced decreased compared to the group without induction (Nurhidajah & Nurrahman, 2017).…”
Section: Resultssupporting
confidence: 93%
“…In another study, giving germinated black rice to STZ-NA induced rats could increase insulin levels by 16.35% (Nurhidajah & Nurrahman, 2017). In this study, the group of DM rats after the intervention showed an increase in insulin levels compared to the group of DM rats without intervention.…”
Section: Resultssupporting
confidence: 43%
“…Furthermore, this study reported that on day 3 (72 hours after STZ-NA induction), the blood glucose levels in the treated rats were above 200 mg/dl, ranging from 379.80-416.07 mg/dl, which indicated that all rats were diabetes mellitus. In accordance with Anwer (2014) 38 ; Nurhidajah & Nurrahman(2016), 40 it was demonstrated that blood glucose levels would be >200 mg/dl after 72 hours STZ-NA administration, and it can be claimed that rats were in diabetes mellitus type 2 already.…”
Section: Resultssupporting
confidence: 68%
“…Insulin resistance was determined using the Homeostasis Model Assessment Insulin Resistance (HOMA-IR) formula (Byun AR et al, 2015), and to determine the level of pancreatic β-cell function strength using the Homeostasis Model Assessment of Pancreatic Beta Cell Function (HOMAβ) formula (Nurhidajah and Nurrahman, 2016).…”
Section: Homeostasis Model Assessment Indexmentioning
confidence: 99%